Фантастические рассказы - Саломатов Андрей Васильевич (Школьная библиотека, 2022)
Экземпляры: ф.9 (2024) / Инвентарный номер: 60121 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 60 / ББК: 84(2Рос=411.2)6